Fogo Project - Credit Union - Joe Batt's Arm - Memorial University of Newfoundland. Extension Service (Producer); National Film Board of Canada (Producer) (National Film Board in cooperation with Memorial University of Newfoundland, 1968)
The formation of the Joe Batt's Arm Cooperative Credit Union is discussed by two of its members, who detail its benefits. Audio fades at 11:06